In vitro investigation of the effect of food texture, particle size, and viscosity on gastric disintegration and emptying. Issue 1 (18th April 2022) - Kong, Fanbin; Tran Do, Duc Huy
Abstract: The objective of this study was to investigate the influence of particle size, texture, and gastric viscosity on food gastric disintegration and emptying rates. In vitro dynamic gastric digestion was conducted for carrots using a dynamic gastric simulation model. The changes in the texture of carrots and other foods as indicated by bulk resistance, the percent solids emptied, and the particle size distribution were used as parameters to study disintegration kinetics and emptying patterns. The influence of viscosity on food emptying was studied on both indigestible particles (amberlite beads) and digestible solids (carrots). The results indicated medium‐size carrot particles (1.40–2.00 mm) had a greater disintegration and a higher amount of emptying rate when compared to larger (2.00–3.34 mm) and smaller (1.14–1.40 mm) carrot particles. A high correlation exists between the final bulk resistance after 120 min digestion and the amount of solids emptied. Increasing viscosity up to values 8.20 Pa·s improved the particle dispersion for amberlite and carrots and increased rates of solids emptying, while further increase in viscosity hindered emptying of amberlite and carrot solids. The variable emptying rates of both indigestible and digestible solids with viscosity were described with a mathematical model based on particle‐emptying coefficient. Abstract : A dynamic in vitro gastric digestion model was used to investigate how food particle size and texture, and gastric viscosity affect food disintegration and emptying. A mathematic model was proposed to predict the change in the emptying rate of solids with viscosity.